Three new species of the Xylophanes crotonis species-group (Lepidoptera: Sphingidae) from Colombia and a neotype designation for Xylophanes aristor - Yenny CORREA-CARMONA (Institute of Entomology, Biology Centre, Czech Academy of Science, 2021)
Three new species of the hawkmoth genus Xylophanes Hübner, 1819 from Colombia are described based on morphological characters and DNA barcodes: Xylophanes camilae Correa-Carmona & Giusti sp. n., Xylophanes pijao Giusti & Correa-Carmona sp. n., and Xylophanes tayrona Correa-Carmona & Giusti sp. n. The new species are compared with the most morphologically similar species within the informal Xylophanes crotonis species-group: Xylophanes aristor (Boisduval, 1870), Xylophanes crotonis (Walker, 1856) and Xylophanes huloti Haxaire & Vaglia, 2008. Diagnoses, distribution maps, photographs of genital structures and habitus are provided for each new species. In addition, a dichotomous key is provided to identify the new species and the most morphologically similar species within the group. To stabilize the nomenclature and fix the taxon concept, a neotype is designated for Xylophanes aristor.